THE IMPACT OF VORTIOXETINE ON SEXUAL FUNCTION: A SYSTEMATIC REVIEW OF AVAILABLE CLINICAL DATA AND PHARMACOLOGICAL MECHANISMS - Mateusz Myśliwiec; Tytus Tyralik; Maciej Karwat; Julia Kular; Oliwia Malec; Justyna Niebylecka; Izabella Michalska; Natalia Glanc; Dominik Sendecki; Grzegorz Zalewski (International Journal of Innovative Technologies in Social Science, 2025)
Background: Sexual dysfunction is a common and often treatment-limiting side effect of antidepressants, especially SSRIs and SNRIs, impacting quality of life, adherence, and clinical outcomes in patients with major depressive disorder (MDD). Objective: This systematic review assesses clinical and neurobiological evidence on the effects of vortioxetine—a multimodal antidepressant—on sexual function, comparing it to other antidepressants and exploring its potential to alleviate SSRI-induced sexual dysfunction. Methods: A systematic literature search was conducted (PubMed, Embase, Web of Science, Cochrane Library) through June 2025, following PRISMA guidelines. Included studies reported on sexual outcomes in adults treated with vortioxetine, using validated tools such as ASEX or CSFQ. Results: Vortioxetine was consistently associated with lower rates of treatment-emergent sexual dysfunction (TESD) than conventional SSRIs and SNRIs. Rates ranged from 1.1% to 16.2%, often similar to placebo and markedly lower than with paroxetine or venlafaxine. Case studies and observational data suggested vortioxetine may also improve pre-existing sexual dysfunction, including post-SSRI sexual dysfunction (PSSD), particularly in libido and orgasmic function. The most favorable outcomes were seen at doses between 5–15 mg/day. Conclusions: Vortioxetine shows a favorable sexual tolerability profile and may reverse SSRI-induced sexual dysfunction. Its multimodal serotonergic activity likely underpins these benefits. While evidence supports its use in patients at risk for or experiencing TESD, more head-to-head trials with standardized outcome measures are needed.